Nanomaterials and Nanotechnology for Composites : Design, Simulation and Applications - Haghi, A. K.; Thomas, Sabu; Pourhashemi, Ali; Hamrang, Abbas; Kłodzińska, Ewa (CRC Press LLC ; Apple Academic Press, 2015)
Annotation